MYC Rearranged Aggressive B-Cell Lymphomas: A Report on 100 Patients of the Fondazione Italiana Linfomi (FIL). Issue 6 (December 2019) - Tisi, Maria Chiara; Ferrero, Simone; Dogliotti, Irene; Tecchio, Cristina; Carli, Giuseppe; Novo, Mattia; Stefani, Piero Maria; Rattotti, Sara; Balzarotti, Monica; Marino, Dario; Pelosini, Matteo; Romano, Alessandra; et al.
Abstract : Supplemental Digital Content is available in the text